The Experience and Impact of Contraceptive Stockouts Among Women, Providers and Policymakers in Two Districts of Uganda - Grindlay, Kate; Turyakira, Eleanor; Kyamwanga, Imelda T.; Nickerson, Adrianne; Blanchard, Kelly (Guttmacher Institute, 2016)
Little is known about the impact of contraceptive stockouts on women and health care providers, or how policymakers perceive and handle such stockouts. METHODS: In May–July 2015, a qualitative study on experiences of contraceptive stockouts was conducted in two districts of Uganda. It comprised three data collection components: eight focus groups with 50 women, 24 individual in-depth interviews with family planning service providers and facility managers, and 11 in-depth interviews with district-level policymakers and decision makers. Data analysis followed the content analysis approach. RESULTS: Contraceptive stockouts were common, particularly for long-term methods and oral contraceptives. For women, the consequences included stress, increased costs, domestic conflict, and unwanted or unplanned pregnancies. Providers reported emotional distress, blame from clients, deterioration of skills and lower demand for their services as a result of stockouts; they also felt unable to address stockouts under current supply systems. Despite the widespread prevalence and adverse impact of stockouts, policymakers reported being unaware of the scope of the problem. CONCLUSIONS: The findings suggest there is a critical need to raise awareness of the issue, reduce stockouts and mitigate their negative consequences. Efforts to eliminate stockouts should include addressing supply chain issues. Raising community awareness and engaging with men on family planning may be ways to deal with the consequences of stockouts.
Keywords: Contraceptive Stockouts; Policymakers; Uganda